Design and Implementation of a Web-Based Child Malnutrition Data Management System at Posyandu Cempaka, Central Lombok - Husni Tamrin (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2025)
The System Information Management (SIM) website of Universitas Qamarul Huda Badaruddin BAGU serves as a digital platform designed to support academic and administrative services. This study aims to evaluate the quality of the website by combining functional testing using the Equivalent Partitioning technique and usability assessment through the System Usability Scale (SUS). Functional testing was performed on key features such as the login page, digital library (DILA), user profile, SISKA academic module, and e-money services. The results indicated that the login feature functioned as expected, while several weaknesses were identified in other modules, including the absence of input restrictions in DILA, incomplete validation in profile forms, and insufficient error handling in SISKA and e-money transactions. The usability evaluation involved 80 respondents from various study programs who completed the SUS questionnaire. The analysis yielded an average score of 46.91, corresponding to Grade D, which reflects low usability. While users appreciated the website’s visual appearance and the ease of checking payments via e-money, concerns were raised regarding navigation, error handling, and the effectiveness of learning support features. Overall, the findings suggest that although the MIS website fulfills its basic functions, significant improvements are needed in terms of input validation, interface design, and user experience. This research contributes practical insights for enhancing the reliability and usability of university information systems and provides a foundation for future development aimed at creating more efficient and user-friendly platforms.